Integrated Ecological Surveys for Agricultural Development in The Arid Zones of India. I. Chohtan Community Development Block in Barmer district of Rajasthan - Gupta, R K; Saxena, S K (Annals of Arid Zone, 2016)
Six agro-ecological zones based on the lad use capability and other ecological features have been delineated for proper utilisation of land in Chohtan community development block of Barmer district. Class I and class II lands for intensive agriculture are not present in the Block Class III and comprising the interdunal land or slightly hummocky area may be put under cultivation occasionally wit new technology of agriculture. A major part of interdunal plains, classified under class IV land, may be put under crops with new technology of drylnd agriculture Depressional areas are classified under class V land which are usually unsuitable for crop cultivation and may be used for pasture development. Class Vi and class VII lands are occupied by steep sand dunes where there is severe wind erosion. These areas are considered unsuitable for forestry and pasture development. The rocky bare areas and saline depressions of the part of rann of Kutch classed as VIII land need protection of the natural vegetation. Vegetation types and pasture communities in each landform studied have been described in detail showing the potential for pastoral development and afforestation. Plants for afforestation , soil conservation, orchard development, fodder and other uses which could be cultivated with different water quality in various agro-ecological zones are recommended.